National income and social accounting - Edey, Harold C.; Peacock, Alan T. (London ; New York : Hutchinson's University Library, 1954)
The authors tried to provide the reader with a rationale of social accounting. They had been more concerned with the examination of meanings, purposes and limitations than with the techniques used in compiling the statistics themselves.
Includes bibliographical references and index.
rpm 21/01/2019
Loans
Keywords: Income; Social accounting; National income--Accounting.